Improving Students’ Writing Ability in Procedure Text Using YouTube Video “Gia Academy” - Wahyuni, Siska Dwi; Wiyaka, Wiyaka (LINGUAMEDIA Journal, 2023)
This research aims to identify the writing skills of students who completed the course without the use of YouTube Video "GIA Academy," the writing skills of students who were provided teaching with the use of YouTube Video "GIA Academy," and the significant differences in writing skills between those students who were provided teaching with YouTube Video "GIA Academy" and those who did not. In this study, quantitative methodology was employed. In a quasi-experiment, two classes were compared as the experimental and control classes consisted of two groups of samples. The findings of this investigation revealed that the experimental class had an average post-test score of 79.72 whereas the control class had an average post-test score of 64.69. The experimental class had a post-test average score of 48.47, while the control class received a score of 16.53, demonstrating a clear distinction between the two classes. The two classes that were taught in different ways have a big difference, although the approach that used YouTube videos from "GIA Academy" to improve students' writing skills worked well enough. The data provided a rather accurate comparison of the test results between the experimental and control groups. In addition to improving students' writing abilities, YouTube video “GIA Academy” to study also changes the learning environment and is regarded as an enjoyable learning approach.